Pemanfaatan Aloe Vera dan Air Beras Sebagai Bahan Alami Pembuatan Hand Sanitizer Pouch Gantung - Pratama, Ine Hanisa; Putri, Silviana Aulia; Fauziah, Putri; Fitriana, Nur (BISMA : Business and Management Journal, 2024)
In this modern era, awareness of the importance of hand hygiene has increased significantly. Good hand hygiene is a fundamental step in preventing the spread of disease, especially in a global pandemic situation like the one we are currently experiencing. One of the most effective ways to keep your hands clean is to use hand sanitizer. However, concerns over the chemicals used in commercial hand sanitizers have prompted interest from the public and researchers in seeking natural and environmentally friendly solutions. Aloe vera and rice water are two natural ingredients known to have antibacterial and antimicrobial properties. The method used in this research is research and development or research and development (R&D). Therefore, research is needed regarding the formulation, effectiveness and safety of hand sanitizers made from aloe vera and rice water. This research also innovated to make a hanging hand sanitizer pouch to make it easier to use.